Possibilities of integrating mathematics and arts in distance education - Elijio, Aistė; Goberytė-Meškauskienė, Agnė (Lietuvos matematikos rinkinys, 2021)
In the context of the world health crisis, distance learning which before that was rarely used in Lithuania became practically universal, causing a number of challenges. Trying to respond to some of them, we started exploring possible advantages of between-subject integration in more effectively using on-line time and increasing interest and motivation of students. The article deals with integrating mathematics and arts in distance learning in basic school. Integrated lesson was created for grade 9, and its results and student reflection showed possibilities presented by such type of education.